Direito à saúde e o dever da fundamentação jurídica : uma abordagem transdisciplinar ancorada na análise crítica do discurso jurídico - Albuquerque Filho, José Antonio de (2011)
The present dissertation is a study of the legal fundaments and the right to health considering the Brazilian Constitutional law, Brazilian Civil Procedure and Critical Discourse Analysis. The general objective consists in investigating the intentions of two judges in the text of their judicial orders and decisions about the same issue in different cases in a period of approximately 48 hours between them. We also analyzed the subjacent ideology in the written words of the judges and the level of subjectivism referring to the different ways they enunciators - utilized the text to the accomplishment of their persuasive arguments considering the existent relation between the text, the co-text and the context. We intended to demonstrate how the enunciative process turns evident the legal fundament establishing between the interlocutors of the linguistic game. The body of the research is constituted of a written judicial order and of two decisions. The methodology adopted considered the dominium of the critical discourse analysis (CDA) with emphasis in the political and ideologic discourse verifying how the linguistics elements conduce to the pretended argumentative orientation in the judicial orders analyzed. The critical discourse analysis makes possible to observe if the decisions were legally fundamented or if there is a deficiency considering the identification of the argumentative operators and of the epistemic models situated in the axis of the subjective idea of who enunciate it. The results found made possible to identify a class of arguments considering the theoretical model developed by Ducrot based in the verbal choices of the judges that turns evident their compromise and the level of intention of each judge